2022
DOI: 10.1021/acs.iecr.1c04599
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Oxidized Microcrystalline Cellulose for Rapid Adsorption of Ammonium

Abstract: As low as 1 ppm concentration of ammonia is sufficient to pose a threat to fish cultured in the fish farm, and therefore effective ammonia removal method is necessary to minimize the ammonia concentration. In this study, cellulose, which is one of the low-cost and highly versatile green polymers, has been modified by TEMPO-mediated oxidation and first applied for ammonia removal from water. For the TEMPOoxidized cellulose of 0.78 mmol/g carboxylate group content, the adsorption capacity was measured to be 8.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…78 The successful oxidation of cellulose was confirmed by the presence of a strong absorption peak at 1603 cm −1 (corresponding to the C�O stretching in carboxyl groups) in the ATR-FTIR spectra of TONC-CP (Figure S5). 79,80 As shown in Figure 6c, TEM images revealed that the prepared TONC-CP possessed a fiber-like network structure with a cross-sectional dimension of 3−10 nm, which was smaller than commercial CNCs (3−12 nm). These findings suggested that the production process could effectively transform the cellulose fibers isolated from CP into cellulose nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…78 The successful oxidation of cellulose was confirmed by the presence of a strong absorption peak at 1603 cm −1 (corresponding to the C�O stretching in carboxyl groups) in the ATR-FTIR spectra of TONC-CP (Figure S5). 79,80 As shown in Figure 6c, TEM images revealed that the prepared TONC-CP possessed a fiber-like network structure with a cross-sectional dimension of 3−10 nm, which was smaller than commercial CNCs (3−12 nm). These findings suggested that the production process could effectively transform the cellulose fibers isolated from CP into cellulose nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Unfortunately, it was difficult to determine the removal rates of the heavy metals and the dye because they reached equilibrium adsorption capacities within a few minutes during the vortexing process. 57 This might be attributed to the excellent dispersibility of ChNC-E1000 (RU) in water. This adsorbent based on eco-friendly EBI-treated chitin nanocrystals with anionic carboxylate groups holds good potential for the removal of various aquatic pollutants from waste streams, such as toxic heavy metals and organic dye cations.…”
Section: Nanoscale Papermentioning
confidence: 99%
“…Many studies have reported on the functional products of cellulose oxidation, but TEMPO-mediated and periodate oxidation reactions stood out due to their enhanced regioselectivity, high degree of substitution, mild conditions, increased yields. Even more, oxidized cellulose thus obtained can be further processed into more complex materials [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%